Integritas Pemimpin dalam Kajian Historis Kritis Yosua 5:13-15 dan Implementasinya Bagi Pemimpin Masa Kini - Sarah Melis Siahaan; Ribka Cristine Sitorus (Tri Tunggal: Jurnal Pendidikan Kristen dan Katolik, 2025)
This article examines Joshua's Integrity in Joshua 5:13-15 with a historical-critical approach to identify the values ​​of leadership with integrity based on Joshua's experience meeting the Commander of the Lord's Host. The research method in the form of a literature study is used to explore the meaning of the Bible text and its relevance to modern leadership challenges. The results of the study show that Joshua's leadership is characterized by full obedience, humility, and respect for divine authority. These values ​​are the foundation for today's leaders in overcoming the temptations of egoism and worldly strategies. The implementation of these values ​​includes recognizing the presence of God, making decisions based on moral principles, and developing humility to create dignified, effective, and common-good-oriented leadership.